2016
DOI: 10.1038/srep28097
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miRNAs are generic and versatile therapeutic monitoring biomarkers in muscular dystrophies

Abstract: The development of medical approaches requires preclinical and clinical trials for assessment of therapeutic efficacy. Such evaluation entails the use of biomarkers, which provide information on the response to the therapeutic intervention. One newly-proposed class of biomarkers is the microRNA (miRNA) molecules. In muscular dystrophies (MD), the dysregulation of miRNAs was initially observed in muscle biopsy and later extended to plasma samples, suggesting that they may be of interest as biomarkers. First, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(68 citation statements)
references
References 54 publications
5
62
1
Order By: Relevance
“…Certainly, further research on wider patient cohorts from different muscular dystrophies would point out if miR-206 levels could discriminate between different forms of muscular dystrophies, as we here notice the ability to discriminate DMD from BMD patients. Moreover, dysregulation of miR-206 has been described in mdx mouse model, following the same pattern, with higher expression on miR-206 observed in serum of the young mice and general decrease of the expression in the later assessment point of the 6 month old mice (21). The elegant study of Israeli et al compared a palette of miRNAs in five mouse models of different muscular dystrophies.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Certainly, further research on wider patient cohorts from different muscular dystrophies would point out if miR-206 levels could discriminate between different forms of muscular dystrophies, as we here notice the ability to discriminate DMD from BMD patients. Moreover, dysregulation of miR-206 has been described in mdx mouse model, following the same pattern, with higher expression on miR-206 observed in serum of the young mice and general decrease of the expression in the later assessment point of the 6 month old mice (21). The elegant study of Israeli et al compared a palette of miRNAs in five mouse models of different muscular dystrophies.…”
Section: Discussionmentioning
confidence: 82%
“…We have not observed the significant difference in the levels of miR-206 in the expanded cohort of patients comparing not ambulant and ambulant patients or significantly higher levels of miR-206 in the very young DMD patients which are in contrast with the results of Zaharieva et al but this differences could be attributed to the different techniques used (i.e., qPCR vs. absolute quantification with ddPCR) or differences in the patient cohorts. As mentioned earlier miR-206 is involved in the process of skeletal muscle injury and regeneration, and consequently, this miRNA has been found dysregulated in patients with other dystrophinopathies (13) and also in the mouse models for different muscular dystrophies (21). Thus, miR-206 may actually be very useful biomarker for dystrophic changes in the muscle.…”
Section: Discussionmentioning
confidence: 88%
“…In addition to being proposed as biomarkers of pathology in neurodegenerative diseases, miRNAs represent attractive therapeutic targets. Current experimental approaches include the use of miRNA mimics (overexpressing miRNA) or antisense oligonucleotides (downregulating miRNA) [64,65]. Numerous proof-of-concept studies employing miRNAs have been reported for neurological disorders including trinucleotide repeat disorders such as Huntington's disease and spinocerebellar ataxia 3 [66,67].…”
Section: Discussionmentioning
confidence: 99%
“…3A). Importantly, dose-response normalization was detected for the myomesin 3 protein [68], and the miRNAs miR-1, miR-133a, miR-206, miR-378a-3p, miR-149-5p, and miR-193b [72]. Especially, the level of myomesin restoration correlated well with the recovery of forces.…”
Section: Biomarkersmentioning
confidence: 87%